Health insurance and inequalities in catastrophic health spending in cancer patients. A cross-sectional study in China - Wenqi Fu; Jufang Shi; Chaojie Liu; Wanqing Chen; Guoxiang Liu; Jie He (Gaceta Sanitaria)
Objective: To determine the role of social health insurance programs in reducing inequality in the incidence and intensity of catastrophic health expenditure (CHE) of cancer patients in China. Method: A convenient sample of 2534 cancer patients treated in nine hospitals in 2015 and 2016 were followed up through face-to-face interviews in March-December 2018. The incidence and intensity (mean positive overshoot) of CHE (≥ 40% household consumption) were calculated. Results: About 72% of cancer patients experienced CHE events after insurance compensation, with the catastrophic mean positive overshoot amounting to 28.27% (SD: 15.83%) of the household consumption. Overall, social insurance contributed to a small percentage of drop in CHE events. Income-related inequality in CHE persisted before and after insurance compensation. Richer patients benefit more than poorer ones. Conclusions: Cancer treatment is associated with high incidence of CHE events in China. The alleviating effect of social health insurance on CHE events is limited. Resumen: Objetivo: Determinar la función de programas del seguro social de salud en reducir las desigualdades en incidencia e intensidad del gasto catastrófico en salud (GCS) en pacientes con cáncer en China. Método: Se realizó seguimiento de una muestra de conveniencia de 2534 pacientes con cáncer atendidos en nueve hospitales en 2015 y 2016, mediante entrevistas cara a cara de marzo a diciembre de 2018. Se calcularon la incidencia y la intensidad (reacción positiva promedio) de GCS (≥40% consumo del hogar). Resultados: Alrededor del 72% de los pacientes con cáncer experimentaron eventos de GCS después de la compensación del seguro; reacción positiva promedio acumulado del 28.27% (DE: 15.83%) del consumo del hogar. En general, el seguro social contribuyó al descenso de un pequeño porcentaje de eventos de GCS. La desigualdad relacionada con ingresos de GCS persistió antes y después de la compensación del seguro. Los pacientes más ricos se benefician más que los pobres. Conclusiones: El tratamiento para el cáncer está asociado con una mayor incidencia de eventos de GCS en China. El efecto mitigante del seguro social de salud es limitado en los eventos de GCS.